Is Trade Openness the Reason of High Energy Demand in China? - Jadoon, Atif Khan; Qasim, Hafiz Muhammad; Sarwar, Ambreen; Khan, Rehan Ahmed; Ali, Muhammad (International Journal of Energy Economics and Policy, 2021)
The present study aims to examine the short-run and long-run impact of China's trade liberalization policies on its energy demand over the period from 1980 to 2018. The results of Autoregressive Distributed Lag approach of co-integration show that energy consumption significantly increases as a result of trade openness and increase in real Gross Domestic Product (GDP). The results of the granger causality test also confirm the unidirectional causality running from trade openness and real GDP to energy demand. The results of the study have an important implication because if China wants to continue its trade liberalization policies then it must increase its energy production. Keywords: Energy Consumption, Gross Domestic Product, Trade Openness, China, Time Series JEL Classifications: C22, F15, L98, Q43 DOI: https://doi.org/10.32479/ijeep.11160